Thermal properties of cryo-ground powder of black pepper (Panniyur 1) - T J Zachariah, P Barnwal, K K Singh, R Kumar, (Journal of Spices and Aromatic Crops, 2013)
The thermal properties of black pepper powder, namely specific heat, thermal conductivity and thermal diffusivity were investigated. The specific heat increased from 225.68 to 4479.53 J kg-1 K-1 with increase in temperature from -150 to 100°C and moisture content from 3.3% to 18.2% dry basis and it showed a second order polynomial relationship with temperature and moisture content. The thermal conductivity increased non-linearly from 0.1161 to 0.1844 W m-1 K-1 with increase in moisture content from 3.3% to 18.2% dry basis at 30oC. The thermal diffusivity increased non-linearly from 10.86 × 10-6 to 17.36 × 10-6 m2 s-1 with increase in moisture content from 3.3% to 18.2% dry basis at 30°C. The thermal conductivity and thermal diffusivity showed quadratic relationships with moisture content. The specific heat was affected significantly with moisture content and temperature (P<0.01). The thermal conductivity and thermal diffusivity were affected significantly by moisture content.